Developments of piezoelectric ultrasonic actuators operating under bending hybrid vibration modes. Issue 5 (4th March 2019) - Xu, Dongmei; Liu, Yingxiang; Shi, Shengjun; Wang, Dingwen; Chen, Weishan; Deng, Jie
ABSTRACT: The exciting methods for the sandwich type piezoelectric ultrasonic actuators used bending hybrid modes are investigated. Five exciting methods are discussed and compared in detail, in which the polarizations and the partitions of the ceramic rings are different. Harmonic analyses are developed to obtain the effects of the exciting methods on the electromechanical coupling factors and the vibration amplitudes. At last, five prototypes are manufactured to verify their differences. Both the simulation and experiment results prove that the exciting method using ceramic rings with four separated partitions achieves great improvements on the efficiency, velocity and force, synchronously.